Opposing relationships of childhood threat and deprivation with stria terminalis white matter. Issue 8 (19th March 2021) - Banihashemi, Layla; Peng, Christine W.; Verstynen, Timothy; Wallace, Meredith L.; Lamont, Daniel N.; Alkhars, Hussain M.; Yeh, Fang‐Cheng; Beeney, Joseph E.; Aizenstein, Howard J.; Germain, Anne
Abstract: While stress may be a potential mechanism by which childhood threat and deprivation influence mental health, few studies have considered specific stress‐related white matter pathways, such as the stria terminalis (ST) and medial forebrain bundle (MFB). Our goal was to examine the relationships between childhood adversity and ST and MFB structural integrity and whether these pathways may provide a link between childhood adversity and affective symptoms and disorders. Participants were young adults ( n = 100) with a full distribution of maltreatment history and affective symptom severity. Threat was determined by measures of childhood abuse and repeated traumatic events. Socioeconomic deprivation (SED) was determined by a measure of childhood socioeconomic status (parental education). Participants underwent diffusion spectrum imaging. Human Connectome Project data was used to perform ST and MFB tractography; these tracts were used as ROIs to extract generalized fractional anisotropy (gFA) from each participant. Childhood threat was associated with ST gFA, such that greater threat was associated with less ST gFA. SED was also associated with ST gFA, however, conversely to threat, greater SED was associated with greater ST gFA. Additionally, threat was negatively associated with MFB gFA, and MFB gFA was negatively associated with post‐traumatic stress symptoms. Our results suggest that childhood threat and deprivation have opposing influences on ST structural integrity, providing new evidence that the context of childhood adversity may have an important influence on its neurobiological effects, even on the same structure. Further, the MFB may provide a novel link between childhood threat and affective symptoms. Abstract : This study provides the first evidence that childhood threat and deprivation have opposing influences on stria terminalis generalized fractional anisotropy (gFA), and novel evidence that different dimensions of childhood adversity may have differential influences on structural integrity or underlying microstructure, even within the same region. Further, our results demonstrate that the medial forebrain bundle may provide a novel link between childhood threat and affective symptoms. Examining how these stress‐related, visceral circuits link childhood adversity to affective symptoms could improve our understanding of mechanisms underlying affective disorders and provide novel targets for intervention.